Identification of high-probability medal-winning events for Malaysian swimmers through analysis of strengths, weaknesses, opportunities and threats - Jin, Seng Thung (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2022)
Link to publisher's homepage at https://www.mohejournal.org/aboutus.asp